2015
DOI: 10.1108/ijebr-11-2013-0185
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant and second-generation Turkish entrepreneurs in Melbourne Australia

Abstract: Purpose – The purpose of this paper is to examine the key differences between first- and second-generation immigrant entrepreneurs in their path to entrepreneurship. The aim of the study is to better understand entrepreneurial motivations amongst immigrants by comparing first- and second-generation entrepreneurs in their motivation for business entry, reliance on co-ethnic market, use of social and financial capital, business planning and marketing practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…Azmat (2013) further described language as a barrier to most immigrants' entrepreneurial endeavours, as it affects their ability to communicate with host country's stakeholders as well as to seek business advice and understand social phenomena. Aside from that, a study by Soydas and Aleti (2015) showed that first and second generations of immigrant entrepreneurs do not take advantage of government agencies' support programs possibly because they are uninformed of the existence of those programmes or because the government has not laid out the right channels to inform them of these programmes.…”
Section: Immigrant Entrepreneurial Issues and Obstaclesmentioning
confidence: 99%
“…Azmat (2013) further described language as a barrier to most immigrants' entrepreneurial endeavours, as it affects their ability to communicate with host country's stakeholders as well as to seek business advice and understand social phenomena. Aside from that, a study by Soydas and Aleti (2015) showed that first and second generations of immigrant entrepreneurs do not take advantage of government agencies' support programs possibly because they are uninformed of the existence of those programmes or because the government has not laid out the right channels to inform them of these programmes.…”
Section: Immigrant Entrepreneurial Issues and Obstaclesmentioning
confidence: 99%
“…When research question two: impact of intention, ability, motivation and business aspiration -on customer and market proximity thesis by way of business growth and development: was addressed, it was similar to a situation found by Soydas and Aleti, (2015) in their study of Turkish immigrant entrepreneurs in Melbourne. This current paper noted the firstgeneration consider organic growth, such as expanding the premises or business offering beyond current limits, helped gain access/entry to new local customers/markets.…”
Section: Discussionmentioning
confidence: 54%
“…It claims that 1.5 generation Chinese immigrants have the advantage of being well-equipped with language skills and knowledge of the host cultural practise (Liu, 2015). However, the 1.5 generation has largely been unexamined in immigrant entrepreneurship research, as most of the research has focused on the differences between the first and second generation of immigrant entrepreneurs (e.g., Masurel & Nijkamp, 2004;Selvarajah et al, 2012;Soydas & Aleti, 2015). Thus, this research pays attention to intergenerational differences among immigrant entrepreneurs.…”
Section: Sociocultural Adaptationmentioning
confidence: 99%
“…However, intergenerational differences among the first generation have been largely Chapter 1: Introduction 13 unexamined in immigrant entrepreneurship research, as most of the research has focused on the differences between the first and second generation of immigrant entrepreneurs (e.g., Masurel & Nijkamp, 2004;Selvarajah et al, 2012;Soydas & Aleti, 2015). In addition, although the ethnic gender role and host country sociocultural context have a suggested influence on immigrant entrepreneurship (Azmat & Fujimoto, 2016), researchers have pointed out that the literature on immigrant entrepreneurship often overlooks issues of gender (Collins & Low, 2010;Robertson & Grant, 2016).…”
Section: Rq2 How Do Cross-cultural Capabilities Impact On Immigrant mentioning
confidence: 99%
See 1 more Smart Citation